PROTOTIPE FASILITAS PELATIHAN KEWIRAUSAHAAN CENGKEH DI PERKEBUNAN JAMBELAER - Indika Kamara Putra; J.M. Joko Priyono Santoso (Jurusan Arsitektur dan Perencanaan, 2023)
Starting from the issues faced by a group of young people from Jambelaer village, Sukabumi, who are seeking work in the city with only junior high school and vocational school diplomas. Some of these youths claim that their fathers were former successful clove entrepreneurs in their village, but went bankrupt due to limited facilities, sales access, and knowledge about clove farming. The farming methods and facilities used by the villagers are still very conventional and highly dependent on weather conditions, resulting in declining harvest yields and selling prices that no longer cover their expenses. Moreover, the farmers lack sufficient knowledge about clove plant care and how to optimize production from clove harvests. As a result, the young farmers have shifted to seeking work in the city, and their clove plantations in the village have been left neglected, as they are considered to have lost their value. This has become a problem because if they are no longer dependent on their natural resources, over time, the importance of clove farming may be forgotten. This project takes the clove plants in their village as the subject of empathy and aims to revitalize clove farming as the main source of income for the village. Therefore, they need a facility for learning and education about clove farming, as well as a processing facility to process their harvests without being too dependent on weather conditions. The proposed architectural solution in this case is a prototype, a building for educational and learning facilities dedicated to everything about clove farming, along with a processing facility. This prototype will be built in the location of the clove plantations owned by the villagers. The